The Berenstain Bears on time - Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012. (New York : Golden Book ; Racine, WI : Western Pub., 1992)
Time flies when Brother Bear and Sister Bear oversleep on a school morning. Can they be ready to catch the school bus on time?
"Berenstain Bears cub club"--Cover.
Keywords: Time -- Fiction; Bears -- Fiction; Stories in rhyme